Analisis Perencanaan Pendidikan SMK Berbasis Standar Kompetensi untuk Menghadapi Tantangan Ketidak Sesuaian Jurusan dengan Lapangan Pekerjaan - Maryam Maryam; Hani Cahya Maulani; Sifa Malihatul Husna; Sri Handayani (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze educational planning at SMK IT Minnatul Huda in Purwakarta Regency with a focus on the suitability of the majors offered with the needs of the workforce. It was found that there was a significant mismatch between the expertise programs offered and the employment profile in the local area, which caused many graduates to have difficulty in getting jobs that match their fields of study. The research method used was a qualitative approach with a case study method, through in-depth interviews with various stakeholders, including schools, teachers, alumni, as well as observation and analysis of related documents. The results of the study indicate that existing educational planning is not yet based on systematic labor market needs data and there is weak active collaboration with the Business World and Industry (DUDI). This study recommends the need to develop a better employment data collection and analysis system, increase partnerships with DUDI, and implement the Indonesian National Work Competency Standards (SKKNI) in the curriculum. With these steps, it is hoped that SMK graduates can be more ready to work, adapt to the dynamics of the labor market, and contribute to the development of competitive human resources in Indonesia.